Nepalese school students' views about sexual health knowledge and understanding. Issue 4 (2nd October 2018) - Acharya, Dev; Thomas, Malcolm; Cann, Rosemary
ABSTRACT: Background : School-based sex education is a strategy that can help prevent sexual and reproductive health-related problems. In Nepal, sex education is taught to secondary school students; however, it is thought that the approach taken to school-based sexual health education (e.g. the type of student-learning materials) is not sufficient to address the needs of the students. Purpose : The aim of this study was to explore the views and beliefs of Nepalese secondary school students about different aspects of sexual health knowledge and understanding, in a school context. Design and Methods : A total of eight focus group discussions were conducted in community-based secondary schools in Nepal. All necessary ethical requirements were obtained before the collection of the data from the schools. The total number of students participating was 78; there were between 9 and 11 students per focus group discussion. The students' ages ranged from 14 to 17 years. Transcriptions of the focus group discussions were made and qualitative, thematic analysis was undertaken. Results : Analysis of the data from the focus group discussions suggested that the majority of the students had curiosity and wished to understand more about sexual health. However, it appeared that the students typically felt too shy and embarrassed to ask sexual health-related questions of their teachers. There also seemed to be a considerable 'communication gap' that prevented the students talking about sexual health with their parents. Students referred to the influences and roles of local cultures, media and the internet. A majority of participants acknowledged the need for knowledge and understanding about sexual and reproductive health. Conclusions : This study suggests opportunities for enhancing the sexual health knowledge and understanding of school students in Nepal by developing suitable and relevant school-based educational approaches. For example, schools could involve the young people themselves in developing and delivering enhanced sex education programmes.